Ecosystem Assessment and Fuzzy Systems Management - Cao, Bing-Yuan; Ma, Sheng-Quan; Cao, Hu-hua (Advances in Intelligent Systems and Computing, 2014)
â_oEcosystem Assessment and Fuzzy Systems Managementâ__ is the edited outcome of the 3rd International Conference on Ecosystem Assessment Management (ICEAM) and the Workshop on the Construction of an Early Warning Platform for Eco-tourism (WCEWPE) in Hainan on May 5-12, 2013, Haikou, China. The 3rd ICEAM and the WCEWPE, built on the success of previous conferences, are major Symposiums for scientists, engineers and logistic management researchers presenting their the latest achievements, developments and applications in all areas of Ecosystem Assessment Management, Early Warning Platform for Eco-tourism and fuzziology. It aims to strengthen relations between industry research laboratories and universities, and to create a primary symposium for world scientists. The book, containing 47 papers, is divided into five parts: â_oEcosystem Assessment, Management and Informationâ__; â_oIntelligent Algorithm, Fuzzy Optimization and Engineering Applicationâ__; â_oSpatial Data Analysis and Intelligent Information Processingâ__; â_oTourism Culture, Development and Planningâ__ and â_oApplication of Operations Research and Fuzzy Systemsâ__.